Lenvatinib with etoposide plus ifosfamide in patients with refractory or relapsed osteosarcoma (ITCC-050): a multicentre, open-label, multicohort, phase 1/2 study. Issue 9 (September 2021) - Gaspar, Nathalie; Venkatramani, Rajkumar; Hecker-Nolting, Stefanie; Melcon, Soledad Gallego; Locatelli, Franco; Bautista, Francisco; Longhi, Alessandra; Lervat, Cyril; Entz-Werle, Natacha; Casanova, Michela; Aerts, Isabelle; Strauss, Sandra J; et al.
Summary: Background: Tyrosine kinase inhibitors have shown activity in osteosarcoma and might enhance the efficacy of chemotherapy. We aimed to determine the recommended phase 2 dose and antitumour activity of lenvatinib with etoposide plus ifosfamide in patients with refractory or relapsed osteosarcoma. Methods: This multicentre, open-label, multicohort, phase 1/2 trial was done at 17 hospitals in six countries. Eligible patients were aged 2–25 years, had relapsed or refractory osteosarcoma, measurable or evaluable disease per Response Evaluation Criteria in Solid Tumors version 1.1, Lansky play–performance score or Karnofsky performance score of 50% or higher, up to one previous VEGF or VEGF receptor-targeted therapy, and a life expectancy of at least 3 months. This study includes a combination dose-finding phase 1 part (cohort 3A) and a phase 2 combination expansion in patients with osteosarcoma (cohort 3B). Lenvatinib was administered orally at a starting dose of 11 mg/m 2 per day, capped at 24 mg per day, and etoposide (100 mg/m 2 per day) plus ifosfamide (3000 mg/m 2 per day) were administered intravenously on days 1–3 of each 21-day cycle for a maximum of five cycles. Lenvatinib monotherapy continued after these five cycles until disease progression, toxic effects, or patient choice to discontinue. The phase 1 primary endpoint was to determine the recommended phase 2 dose by evaluating dose-limiting toxicity and the phase 2 primary endpoint was progression-free survival at 4 months. Progression-free survival was measured in the full analysis set, which included all patients enrolled for efficacy outcomes; safety was assessed in all patients who received any study drug. This study is registered with ClinicalTrials.gov, NCT02432274. Findings: 30 patients were screened for enrolment into cohort 3A between May 9, 2016, and June 3, 2019, and 22 patients for enrolment into cohort 3B between Sept 13, 2018, and July 18, 2019. Eight patients from cohort 3A and two from cohort 3B were ineligible for enrolment in the study. In phase 1, dose-limiting toxicities were observed in three patients (one in the lenvatinib 11 mg/m 2 combination group and two in the 14 mg/m 2 combination group) and the recommended phase 2 dose was determined as lenvatinib 14 mg/m 2 per day (with daily dose cap of 24 mg) and etoposide 100 mg/m 2 per day plus ifosfamide 3000 mg/m 2 per day administered intravenously on days 1–3 of each 21-day cycle for a maximum of five cycles. 35 patients from phase 1 (cohort 3A; n=15) and phase 2 (cohort 3B; n=20) were treated at the recommended phase 2 dose and their results were pooled. Progression-free survival at 4 months was 51% (95% CI 34–69) in 18 of 35 patients per the binomial estimate. The most common grade 3–4 treatment-emergent adverse events were neutropenia (27 [77%] of 35), thrombocytopenia (25 [71%]), anaemia (19 [54%]), and decreased white blood cell count (19 [54%]). 26 [74%] of 35 patients had serious treatment-emergent adverse events and no treatment-related deaths occurred. Interpretation: Lenvatinib with etoposide plus ifosfamide shows promising antitumour activity with no new safety signals in patients with refractory and relapsed osteosarcoma. These findings warrant further investigation in an ongoing randomised phase 2 study (NCT04154189). Funding: Eisai and Merck Sharp & Dohme.